Acute Poisoning in Children in Bahia, Brazil - Dilton Rodrigues Mendonça MSc; Marta Silva Menezes PhD; Marcos Antônio Almeida Matos PhD; Daniel Santos Rebouças MD; Jucelino Nery da Conceição Filho BS; Reginara Souza de Assis MD; Leila Carneiro (SAGE Publishing, 2016)
Acute poisoning is a frequent accident in childhood, particularly in children under 4 years of age. This was a descriptive study with data collected from standardized forms of the Poison Control Center and patient record charts. All the cases of acute poisoning in children aged 0 to 14 years during the period 2008 to 2012 were selected. The variables studied comprised characteristics of the events and toxic agents, clinical development, and outcome. A total of 657 cases of acute poisoning, with higher frequency in the age-group from 1 to 4 years (48.7%) and male sex (53.4%), were recorded. The occurrences were accidental in 92% of the cases, and 5.8% were due to suicide attempts. Among the toxic agents, medications (28.5%), venomous animals (19.3%), nonvenomous animals (10%), household cleaning products (9.0%), and raticide agents (8.7%) predominated. The majority of cases were characterized as light (73.5%) and around 18% required hospitalization, and there was low lethality (0.5%).